Identification of a domain required for oncogenic activity and transcriptional suppression by v-erbA and thyroid-hormone receptor alpha. - Damm, K (1993)
v-erbA, a mutated version of the chicken thyroid hormone (TH) receptor type alpha, can inhibit hormonal induction of target genes. In addition, v-erbA acts as a constitutive repressor of the basal promoter activity. In vivo, v-erbA can arrest the differentiation of erythroid precursor cells and suppresses transcription of erythrocyte-specific genes. We show that the v-erbA protein of the transformation-defective avian erythroblastosis virus mutant (AEVtd359) fails to suppress basal transcription level and exhibits impaired ability in antagonizing the TH and retinoic acid response. The inactivating mutation is a 1-nt change leading to a Pro-->Arg replacement in the "hinge region" of v-erbA protein. Introducing this mutation in the context of TH receptor alpha selectively inactivates the suppressor function, while hormone-binding and transcriptional-activation properties are unaffected. These data suggest that trans-repression rather than a dominant negative block of TH-receptor or retinoic acid-receptor activation may represent the primary molecular property underlying erbA oncogenesis.